Ban this book - Gratz, Alan, 1972- (New York : Starscape, 2017)
A fourth grader fights back when From the Mixed-Up Files of Mrs. Basil E. Frankweiler by E. L. Konigsburg is challenged by a parent and the school board removes it from the shelves of her school library. Amy Anne is shy and soft-spoken, but don't mess with her when it comes to her favorite book in the whole world. Amy Anne and her friends start a secret banned books locker library and make up ridiculous reasons to ban every single book in the library to make a point, and take a stand against censorship.
Includes activity guides.
Keywords: Prohibited books -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; Problem solving -- Juvenile fiction; Censorship -- Juvenile fiction